Numerical optimization of the extra-cavity diamond Raman laser in the multi-phonon absorption band - Shao, Zhenhua; Li, Bei; Chen, Hongzhi; Cao, Jun (Frontiers in Physics, 2022)
The physical process of stimulated Raman scattering (SRS) in the diamond and the performance of the Raman laser in the multi-phonon absorption band of 2.5–3 μm were theoretically studied. A theoretical model for the external-cavity diamond Raman laser emitting at the waveband was built based on the Raman coupled-wave equation and boundary conditions. Raman laser output characteristics such as lasing threshold, input–output, and temporal behavior of Stokes conversion were investigated and theoretically simulated by varying the values of the length of the diamond and the transmittance of the output coupler. The numerical modeling shows that to reduce the impact of the multi-phonon absorption and obtain a higher conversion efficiency, it is necessary to appropriately increase the output coupling of the cavity. Taking the 3 μm diamond Raman laser optimization as an example, it is predicted that the conversion efficiency of 10% could be obtained with a diamond length of 1 cm, a transmittance of 69%, and a pump intensity of 1.2 GWcm−2. The theoretical model also could be used to investigate other wavelengths of the external-cavity diamond Raman laser and be helpful for the optimum design of diamond Raman lasers in the mid-infrared band.